Strategic Orientation, International Exchange, and Cooperation in Running Schools - Deng, Linzi (Journal of Theory and Practice of Management Science, 2023)
Under one belt, one road, one of the "one belt, one road" construction path, the concept of "one belt and one road" education community has been presented to everyone's vision. In terms of international exchanges and cooperation, we have also met greater opportunities and challenges. In order to meet one's needs of one belt, one road, the universities also began to promote the harmonious development of regional education based on equality, tolerance, reciprocity, and activity. We should strengthen the spirit of cooperation, realize the sharing of educational resources, and protect the common feelings of the people. Therefore, this paper first puts forward the main problems to be explored, and then, combined with the actual development needs, constructs the construction path of international exchange and cooperation in running schools.